Learning English through YouTube: a Narrative Exploration of Students’ Psychological Journey - Husin; Asfihana, Raida (Proceeding International Conference on Education, 2025)
This research investigates the psychological factors influencing students when using YouTube videos as a medium for learning English in the classroom setting. Adopting a qualitative method with a narrative inquiry approach, the study examines how YouTube impacts students’ motivation, interest, attitudes, talents, intelligence levels, and anxiety, along with the obstacles they encounter. Data were gathered through in-depth interviews with ten eighth-grade students from SMP Hidayatullah Martapura, South Kalimantan, who learned English through YouTube videos shared by their teacher. The results indicate that YouTube videos noticeably enhance students' psychological engagement in learning English. The majority of students experienced increased motivation, greater interest, and more positive attitudes toward the content. The audiovisual nature of the videos was found to aid comprehension and alleviate learning anxiety. Despite these benefits, challenges such as limited technological access, inconsistent internet connection, disruptive ads, and difficulty in locating suitable educational material were also identified. This study emphasizes that while YouTube videos can be a powerful tool in language learning, their success relies on carefully selected content, active teacher involvement, and adequate infrastructure. The findings provide important insights for educators, schools, and researchers seeking to use digital media to improve language acquisition in a psychologically aware and effective way.